Does contract farming improve profits and food safety? Evidence from tomato cultivation in Nepal - Kumar, Anjani; Roy, Devesh; Tripathi, Gaurav; Joshi, Pramod Kumar; Adhikari, Rajendra Prasad (Emerald Publishing Limited, 2018)
The purpose of this paper is to quantify the benefits of contract farming (CF) on farmers’ income and adoption of food safety measures (FSMs) at the farm level. The paper also investigates the determinants of participation in CF.The study is based on a survey of 600 tomato farmers from Nepal. Descriptive statistics, regression analysis (using instrumental variable) and propensity score matching have been used to accomplish the objectives of the study.The study found that the CF ensures higher returns to farmers as well as higher adoption of FSMs at the farm level. The contract farmers earned about 38 per cent higher net returns and had 38 per cent higher adoption of FSM as compared to independent farmers. Caste, occupation, farm size and cropping intensity significantly affected farmers’ participation in CF.The analysis based on cross-section data has limitations to consider unobserved farmer-level individual heterogeneity.This study will provide an empirical base to promote CF in Nepal. The study will also contribute to bridge the gap in literature on the drivers of CF and its impact on smallholders’ income and compliance with FSM in Nepal.